'With almost electric speed': mapping African American abolitionists in Britain and Ireland, 1838–1847. (3rd July 2019) - Murray, Hannah-Rose
ABSTRACT: African American abolitionists made an indelible mark on nineteenth-century transatlantic society: their lectures were held in famous meeting halls, taverns, theatres, churches, and the private parlour rooms of wealthy patrons across the British Isles. This article will demonstrate how digital mapping techniques reveal not only the extent of how far African Americans travelled, but also how visualizing their tours can lead to new avenues of research. Digital mapping can reinvigorate scholarship on transatlantic activism by providing original insights into journeys by men such as Frederick Douglass and Moses Roper.